2016
DOI: 10.1136/thoraxjnl-2016-208544
|View full text |Cite
|
Sign up to set email alerts
|

Relieving dyspnoea by non-invasive ventilation decreases pain thresholds in amyotrophic lateral sclerosis

Abstract: Relieving dyspnoea by NIV in patients with ALS having respiratory failure is associated with decreased pressure pain thresholds. Clinical implications have yet to be determined, but this observation suggests that patients with ALS could become more susceptible to pain after the institution of NIV, hence the need for reinforced attention towards potentially painful diagnostic and therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…In addition, the age at the time of the requirement for transition to TIV was an important factor that influenced decision making. 35,36 The difference between ages at TIV(+) and TIV(−) was not significant, and the ALS patients tended to refuse TIV when they were older because NIV could prolong their survival.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, the age at the time of the requirement for transition to TIV was an important factor that influenced decision making. 35,36 The difference between ages at TIV(+) and TIV(−) was not significant, and the ALS patients tended to refuse TIV when they were older because NIV could prolong their survival.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies reported that long‐term NIV support decreased QOL due to sleep problems and a decreased pain threshold, which may lead to the accumulation of social restrictions and physiopsychological burdens in patients as well as caregivers, causing hesitation to transition from NIV to TIV. In addition, the age at the time of the requirement for transition to TIV was an important factor that influenced decision making . The difference between ages at TIV(+) and TIV(−) was not significant, and the ALS patients tended to refuse TIV when they were older because NIV could prolong their survival.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study in ALS suggested that mechanical ventilation, while corrects hypoventilation and alleviates dyspnoea, might increase the susceptibility to pain in terms of reduced pain pressure threshold. 48 Dyspnoea is known to activate the diffuse nociceptive inhibitory control as demonstrated by its inhibitory effect on painful stimuli (e.g. laser evoked potentials) 49 and nociceptive spinal flexion reflex (e.g.…”
Section: Types Of Painmentioning
confidence: 99%
“…A strong correlation between dyspnoea and pain has been described in patients who are effectively relieved by NIV. Relieving dyspnoea by NIV in patients with ALS having respiratory failure is associated with decreased pressure pain thresholds …”
Section: Palliative Care and Discontinuation Of Nivmentioning
confidence: 99%